Clinical Evaluation of Paraspinal Mini-Tubular Lumbar Decompression and Minimally Invasive Transforaminal Lumbar Interbody Fusion for Lumbar Spondylolisthesis Grade I with Lumbar Spinal Stenosis: A Cohort Study - Liang, Zeyan; Xu, Xiongjie; Rao, Jian; Chen, Yan; Wang, Rui; Chen, Chunmei (Frontiers in Surgery, 2022)
Objective: To investigate the clinical outcome data and difference in efficacy between paraspinal mini-tubular lumbar decompression (PMTD) and minimally invasive transforaminal lumbar interbody fusion (MIS TLIF) in the treatment of degenerative lumbar spondylolisthesis grade I with lumbar spinal stenosis (DLS-I-LSS). Methods: Patients with DLS-I-LSS, who underwent PMTD or MIS TLIF from September 2017 to March 2020, were included retrospectively. The follow-up period was 24 months after surgery. Outcome measurements included the Oswestry disability index (ODI) score, visual analog scale (VAS) low back pain score, VAS leg pain score, surgical data, and adverse events. Results: A total of 104 patients with DLS-I-LSS were included in this study. The average improvement in ODI at 12 months (2.0%, 95% CI -5.7% to 1.8%; P =0.30) and 24 months (1.7%, 95% CI -2.7% to 6.1%; P=0.45) after surgery between the two groups were not statistically significant. The improvement in VAS low back pain score after 24 months and improvement in VAS leg pain score were not significantly different between the two groups. Compared with the PMTD group, the MIS TLIF group had more estimated blood loss and longer hospital stays. The cumulative reoperation rates were 5.66% and 1.96% in the MIS TLIF and PMTD groups, respectively (P=0.68). The results of multivariate analysis showed that BMI, diabetes, and baseline ODI score were the main factors influencing the improvement in ODI in patients with DLS-I-LSS after minimally invasive surgery, accounting for 50.5% of the total variance. Conclusions: The clinical effectiveness of PMTD was non-inferior to that of MIS TLIF for DLS-I-LSS; however, there was a reduced duration of hospital stay, operation time, blood loss, and hospitalization costs in the PMTD group. BMI, presence or absence of diabetes and baseline ODI score were influencing factors for the improvement of ODI. (Trial Registration：ChiCTR2000040025)